Does Covid-19 pandemic influence the sustainability of health insurance membership among informal workers in Indonesia? - Aji, Budi; Rachmatika, Hasna Tri; Maharani, Afrina; Intiasari, Arih Diyaning; Anandari, Dian; Malik, Ahmad Azam (Insights in Public Health Journal, 2023)
Background This study aims to find out the impact felt by informal sector workers due to the Covid-19 pandemic and their efforts to maintain the membership of the NHI program. Methods This was qualitative research with a case study approach. Eight study participants had been selected for this study. All interviews then transcribing verbatim for further data analysis. The analysis was conducted by using thematic networks approach. Results There were four themes emerged from the analysis. The themes covering issue about: i) the influence of the Covid-19 pandemic on the informal sector; ii) coping strategies for maintaining NHI premium payment; iii) the role of social capital for supporting informal workers during Covid-19 pandemic; and iv) policy recommendation for protecting the informal sector for maintaining NHI membership. Conclusions This study highlights the strategic position of cooperatives in supporting their members from the burden of NHI premium payment. Government is needed to support the informal workers product so can improve the economic condition these such population.